Kepemimpinan Kepala Sekolah dalam Meningkatkan Kinerja Guru PAI MTsN 1 Pekanbaru - Khoironi (Milenial: Journal for Teachers and Learning, 2024)
The aim of this research is to examine the principal's leadership which includes: (1) To find out the principal's strategy in improving the performance of PAI teachers at MTsN 1 Pekanbaru; (2) To find out the obstacles faced by school principals in improving the performance of PAI teachers at MTsN 1 Pekanbaru; (3) To find out the solutions provided by the school principal in improving the performance of PAI teachers at MTsN 1 Pekanbaru. In this research, research methods were used: (1) Research approach: qualitative; (2) Type of research: case study; (3) Data sources: school principals, PAI teachers, library and document sources; (4) Sampling: Purposive sampling, snowball sampling; (5) Data collection methods: observation, interviews, and documentation; (6) Data analysis techniques: deductive, inductive and comparative. After the author conducted research using the method above, the author found the research results: (1) The principal's strategy in improving the performance of PAI teachers at MTsN 1 Pekanbaru by implementing strategies including: increasing discipline, providing motivation, giving awards and recognition, openness, kinship and deliberation ; (2) The obstacles faced by school principals in improving the performance of PAI teachers at MTsN 1 Pekanbaru include: limited facilities, poor teacher commitment, teachers carrying out other efforts which sometimes interfere with their official duties, and mastery of the material